Watershed Continuum Monitoring Approach: combining multiple water quality patterns along stream and river flowpaths to track sources, pathways, and processing of pollutants - Sujay S. Kaushal; Ashley E. Mon; Stanley B. Grant; Paul M. Mayer; Aaron J. Porter; Andrew J. Sekellick; Jason H. Chase; Shantanu V. Bhide; John D. Jastram; Tamara A. Newcomer-Johnson; Sydney A. Shelton; Alexis M. Yaculak; et al. (Ecological Engineering, 2026)

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Integrated rock-physics-machine-learning analysis for lithofacies and fluid characterization in the North Slope, alaskan clastic reservoir - Emmanuel Awucha Igwe; John Akor Yakubu; Ngozi Agatha Okwesili; Mirianrita Ngozi Ugwu; Daniel Chinomnso Umejiaku; Johnson Cletus Ibuot; Johnson Uchenna Abangwu; Dominic Chukwuebuka Obiegbuna; Chukwudike Gabriel Okeugo; Chibueze Kenneth Diala; Desmond Okechukwu Ugbor; Daniel Nnaemeka Obiora (Computational Geosciences, 2026)

Diversity and functional group composition drive biogeographic patterns in marine biogenic structural complexity - Dean S. Janiak; Matthew A. Whalen; David R. Branson; Soledad Álvarez; Gail V. Ashton; Nicholas M. Bartkowiak; Simon J. Brandl; João Canning‐Clode; Jordan M. Casey; Max C. N. Castorani; Carolina César‐Ávila; Rachel Collin; et al. (Ecology, 2026)
Biogenic structural complexity is a key driver of biodiversity and ecosystem functioning, yet its ecological and environmental determinants remain poorly understood across broad biogeographic scales. Here, we conducted standardized 90‐day field experiments at 16 coastal sites, spanning a 41‐degree latitudinal gradient, using naturally assembled marine fouling communities on settlement panels. We measured rugosity as our metric of biogenic structural complexity and modeled its relationship with species richness, community composition, community growth rates, and abiotic conditions (salinity and temperature). Species richness increased with temperature and salinity and declined with latitude, with more diverse communities exhibiting greater biogenic complexity due to increased morphological variation. At high‐latitude sites, low‐diversity communities dominated by arborescent bryozoans also had increased complexity. Structural equation models showed that abiotic conditions influenced growth and composition, which in turn shaped complexity. Warmer, saltier sites promoted richness‐driven complexity, while colder conditions favored structurally important dominant taxa. We found that biodiversity is important not only as a beneficiary of complexity but also as a contributor to complexity itself within fouling communities. Our results also demonstrate that both species richness and functional group identity regulate biogenic complexity across environmental gradients, underscoring biodiversity's role in supporting ecosystem structure and resilience in the face of increasing global change. Understanding these relationships is essential for biodiversity conservation and the management of marine ecosystems facing increasing anthropogenic pressures.

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Unveiling the Hidden Complexity: Morphological Polymorphisms and Cryptic Diversity in a Zooxanthellate Massive Coral Species of the Genus Favites (Scleractinia, Merulinidae) - Daigo Kishi; Kenneth G. Johnson; Hironobu Fukami (Zoologica Scripta, 2026)
The species‐level identification of zooxanthellate scleractinian corals based on morphology is extremely difficult. This difficulty can potentially lead to inaccurate conclusions due to species misidentification, posing a risk in applied research. In this study, we integrated detailed morphological and molecular phylogenetic analyses to investigate the hidden morphological polymorphisms of Favites valenciennesii , a species primarily characterised by the presence of groove‐and‐tube structures between corallites. Because F. valenciennesii shares morphological similarities with related taxa, its taxonomic status has remained unresolved for over 170 years. To address this, we combined Random Forest‐based feature selection with multivariate analysis to identify species‐specific morphological characteristics of F. valenciennesii . This approach classified F. valenciennesii into four morphologically distinct types (types A–D). Molecular phylogenetic analysis further revealed that two types (A and B) belong to the genus Favites , while the other two types (C and D) belong to Dipsastraea . Within Favites , two distinct clades corresponded to types A and B. Comparison with type specimens and taxonomic studies confirmed that type A represented true F. valenciennesii , while type B represented Favites irregularis comb. nov. Although types C and D were not formally described, the results suggested that they likely represent undescribed species of Dipsastraea . The integrated approach used in this study provides highly accurate species identification and offers significant potential for improving coral taxonomy.

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Runoff and soil erosion on woodland-encroached sagebrush rangeland under simulated rainfall and concentrated flow conditions - Viktor O. Polyakov; C. Jason Williams; Justin C. Johnson; Erin L. Phelps; Raven Chavez; Philip Heilman; William A. Rutherford; Osama Z. Al-Hamdan; Sayjro K. Nouwakpo; Jia Hu; Kenneth E. Spaeth; Samuel Anderson (CATENA, 2026)

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Inter-method differences (SIMS vs. IRMS) in oxygen isotope fractionation: insights from Chinook salmon otoliths - Kohma Arai; Malte Willmes; George E. Whitman; Kenneth W. Zillig; Cassidy J. Cooper; Nozomi Matsuda; Elizabeth A. Bell; Kevin D. McKeegan; Levi S. Lewis; Carson A. Jeffres; Rachel C. Johnson (Geochimica et Cosmochimica Acta, 2025)

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Decadal change in deep-ocean dissolved oxygen in the North Atlantic Ocean and North Pacific Ocean - Henry A. Ruhl; Christine L. Huffard; Monique Messié; Thomas P. Connolly; Thomas Soltwedel; Frank Wenzhöfer; Rodney J. Johnson; Nicholas R. Bates; Susan Hartman; Anita Flohr; Edward W. Mawji; David M. Karl; et al. (Deep Sea Research Part I: Oceanographic Research Papers, 2025)

Network of networks: Time series clustering of AmeriFlux sites - David E Reed; Housen Chu; Brad G. Peter; Jiquan Chen; Michael Abraha; Brian Amiro; Ray G. Anderson; M. Altaf Arain; Paulo Arruda; Greg A. Barron-Gafford; Carl Bernacchi; Daniel P. Beverly; et al. (Agricultural and Forest Meteorology, 2025)

Advancing ocean monitoring and knowledge for societal benefit: the urgency to expand Argo to OneArgo by 2030 - Virginie Thierry; Hervé Claustre; Orens Pasqueron de Fommervault; Nathalie Zilberman; Kenneth S. Johnson; Brian A. King; Susan E. Wijffels; Udaya T. V. S. Bhaskar; Magdalena Alonso Balmaseda; Mathieu Belbeoch; Marine Bollard; Jacqueline Boutin; et al. (Frontiers in Marine Science, 2025)
The ocean plays an essential role in regulating Earth’s climate, influencing weather conditions, providing sustenance for large populations, moderating anthropogenic climate change, encompassing massive biodiversity, and sustaining the global economy. Human activities are changing the oceans, stressing ocean health, threatening the critical services the ocean provides to society, with significant consequences for human well-being and safety, and economic prosperity. Effective and sustainable monitoring of the physical, biogeochemical state and ecosystem structure of the ocean, to enable climate adaptation, carbon management and sustainable marine resource management is urgently needed. The Argo program, a cornerstone of the Global Ocean Observing System (GOOS), has revolutionized ocean observation by providing real-time, freely accessible global temperature and salinity data of the upper 2,000m of the ocean (Core Argo) using cost-effective simple robotics. For the past 25 years, Argo data have underpinned many ocean, climate and weather forecasting services, playing a fundamental role in safeguarding goods and lives. Argo data have enabled clearer assessments of ocean warming, sea level change and underlying driving processes, as well as scientific breakthroughs while supporting public awareness and education. Building on Argo’s success, OneArgo aims to greatly expand Argo’s capabilities by 2030, expanding to full-ocean depth, collecting biogeochemical parameters, and observing the rapidly changing polar regions. Providing a synergistic subsurface and global extension to several key space-based Earth Observation missions and GOOS components, OneArgo will enable biogeochemical and ecosystem forecasting and new long-term climate predictions for which the deep ocean is a key component. Driving forward a revolution in our understanding of marine ecosystems and the poorly-measured polar and deep oceans, OneArgo will be instrumental to assess sea level change, ocean carbon fluxes, acidification and deoxygenation. Emerging OneArgo applications include new views of ocean mixing, ocean bathymetry and sediment transport, and ecosystem resilience assessment. Implementing OneArgo requires about $100 million annually, a significant increase compared to present Argo funding. OneArgo is a strategic and cost-effective investment which will provide decision-makers, in both government and industry, with the critical knowledge needed to navigate the present and future environmental challenges, and safeguard both the ocean and human wellbeing for generations to come.

Modeling Wetland Resources for Spring Migratory Waterbirds Under Different Agricultural Management Scenarios in the Iowa Portion of the Prairie Pothole Region, USA - Mark E. Mitchell; Michael J. Anteau; Aaron T. Pearse; Tammy Newcomer-Johnson; Jay Christensen; William Crumpton; Brian Dyson; Timothy J. Canfield; Matthew Helmers; David Green; Kenneth J. Forshay (Wetlands, 2025)
Constructed water quality wetlands, designed to accept tile drainage and surface runoff, are a promising solution for reducing surface water nutrient loading from agricultural systems. In addition to their water quality benefits, these systems may also offset losses of migratory waterbird stopover sites resulting from historical and future agricultural drainage modernization. To assess this possibility, we developed spatially explicit habitat models informed with expert opinion to explore the: 1) potential of water quality wetlands to provide suitable stopover resources for waterbirds during spring migration; and 2) the extent these wetlands can offset likely losses of stopover resources due to drainage modernization. We focused our modeling on the Iowa portion of the Prairie Pothole Region of North America as it was a historically important area within this vital region for waterbirds, but it has experienced widespread subsurface drainage. Model results indicate that unmitigated drainage modernization is likely to have a large negative effect on spring migratory resources for dabbling ducks and shorebirds and minimal effect on diving ducks. Water quality wetland installations are likely to provide habitat for dabbling and diving ducks, but wetland installation is unlikely to completely offset habitat losses for dabbling ducks and shorebirds. Drainage modernization aside, our results indicate that water quality wetlands can address several environmental issues associated with agricultural expansion and intensification by improving water quality and providing wetland resources for waterbirds and other organisms. Field-scale research is needed to validate these results.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

The seasonal patterns of hydrographic and biogeochemical variables in the Ross Sea: A BGC-Argo analysis - Ruobing Cao; Walker O. Smith; Yisen Zhong; Stephen Riser; Kenneth S. Johnson; Lynne Talley (Deep Sea Research Part II: Topical Studies in Oceanography, 2025)

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Controls on spatial variation in porewater methane concentrations across United States tidal wetlands - Erika L. Koontz; Sarah M. Parker; Alice E. Stearns; Brian J. Roberts; Caitlin M. Young; Lisamarie Windham-Myers; Patricia Y. Oikawa; J. Patrick Megonigal; Genevieve L. Noyce; Edward J. Buskey; R. Kyle Derby; Robert P. Dunn; et al. (Science of The Total Environment, 2024)

A content analysis of parents’ reflections on pathogenic and uncertain pediatric oncology germline sequencing results - Katianne M. Howard Sharp; Mary Egan Clark; Niki Jurbergs; Annastasia Ouma; Lynn Harrison; Leslie Taylor; Kayla Hamilton; Rose B. McGee; Regina Nuccio; Stacy Hines-Dowell; Jami S. Gattuso; Michelle Pritchard; et al. (Familial Cancer, 2024)

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Shifting groundwater fluxes in bedrock fractures: Evidence from stream water radon and water isotopes - Keira Johnson; John N. Christensen; W. Payton Gardner; Matthias Sprenger; Li Li; Kenneth H. Williams; Rosemary W.H. Carroll; Nicholas Thiros; Wendy Brown; Curtis Beutler; Alexander Newman; Pamela L. Sullivan (Journal of Hydrology, 2024)

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Reproductive factors, hormonal interventions, and gastric cancer risk in the Stomach cancer Pooling (StoP) Project - Minkyo Song; Harindra Jayasekara; Claudio Pelucchi; Charles S. Rabkin; Kenneth C. Johnson; Jinfu Hu; Domenico Palli; Monica Ferraroni; Linda M. Liao; Rossella Bonzi; David Zaridze; Dmitry Maximovitch; et al. (Cancer Causes & Control, 2024)

Seasonality modulates particulate organic carbon dynamics in mid-latitudes of South Pacific and South Atlantic Oceans - Mariana B. Bif; Jacqueline S. Long; Kenneth S. Johnson (Journal of Marine Systems, 2024)

Turbid reefs experience lower coral bleaching effects in NE Borneo (Sabah, Malaysia) - Allia Rosedy; Isabel Ives; Zarinah Waheed; Muhammad Ali Syed Hussein; Sindia Sosdian; Kenneth Johnson; Nadia Santodomingo (Regional Studies in Marine Science, 2023)

The Southern Ocean carbon and climate observations and modeling (SOCCOM) project: A review - Jorge L. Sarmiento; Kenneth S. Johnson; Lionel A. Arteaga; Seth M. Bushinsky; Heidi M. Cullen; Alison R. Gray; Roberta M. Hotinski; Tanya L. Maurer; Matthew R. Mazloff; Stephen C. Riser; Joellen L. Russell; Oscar M. Schofield; et al. (Progress in Oceanography, 2023)

A review of ecosystem services from edge-of-field practices in tile-drained agricultural systems in the United States Corn Belt Region - Mark E. Mitchell; Tammy Newcomer-Johnson; Jay Christensen; William Crumpton; Brian Dyson; Timothy J. Canfield; Matthew Helmers; Kenneth J. Forshay (Journal of Environmental Management, 2023)

Is the Coral Triangle’s future shown in a Pliocene reef gap? - G. William M. Harrison; Nadia Santodomingo; Kenneth G. Johnson; Willem Renema (Coral Reefs, 2023)
Although Pliocene temperature and pCO2 are similar to those predicted in the IPPC RCP4.5 scenario, the distribution of coral reefs in the center of maximum coral diversity, the Coral Triangle, during this period has not been explored. We discovered a significantly lower occurrence of reefs during the Pliocene, which we refer to as the Pliocene Reef Gap, but this decrease was not associated with a drop in coral genus richness. While some of the multiple local causes that drove this decline, such as sea level rise, are analogs to drivers of Anthropocene reef decline, neither warming nor increasing pCO2 are among them.

Geochemical and mechanical interactions within sheet-like granite intrusion during stress-field changeover (Moldanubian Batholith; Central European Variscides) - Tadeáš Hájek; Kryštof Verner; Václav Špillar; David Buriánek; Kenneth Johnson (Lithos, 2023)

A census of quality-controlled Biogeochemical-Argo float measurements - Adam C. Stoer; Yuichiro Takeshita; Tanya Lea Maurer; Charlotte Begouen Demeaux; Henry C. Bittig; Emmanuel Boss; Hervé Claustre; Giorgio Dall’Olmo; Christopher Gordon; Blair John William Greenan; Kenneth S. Johnson; Emanuele Organelli; et al. (Frontiers in Marine Science, 2023)
Biogeochemical- (BGC-) Argo aims to deploy and maintain a global array of autonomous profiling floats to monitor ocean biogeochemistry. With over 250,000 profiles collected so far, the BGC-Argo network is rapidly expanding toward the target of a sustained fleet of 1,000 floats. These floats prioritize the measurement of six key properties: oxygen, nitrate, pH, chlorophyll-a, suspended particles, and downwelling light. To assess the current biogeochemical state of the ocean, its variability, and trends with confidence, it is crucial to quality control these measurements. Accordingly, BGC-Argo maintains a quality control system using manual inspection and parameter-specific algorithms for flagging and adjusting data. In this study, we provide a census of the quantity and quality of measurements from BGC-Argo based on their quality flagging system. The purpose of this census is to assess the current status of the array in terms of data quality, how data quality has changed over time, and to provide a better understanding of the quality-controlled data to current and future users. Alongside increasing profile numbers and spatial coverage, we report that for most parameters between 80 and 95% of the profiles collected so far contain high-quality BGC data, with an exception for pH. The quality of pH profiles has seen a large improvement in the last five years and is on track to match the data quality of other BGC parameters. We highlight how BGC-Argo is improving and discuss strategies to increase the quality and quantity of BGC profiles available to users. This census shows that tracking percentages of high-quality data through time is useful for monitoring float sensor technology and helpful for ensuring the long-term success of BGC-Argo.

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

California's ambitious greenhouse gas policies: Are they ambitious enough? - Kenneth C. Johnson (Energy Policy, 2023)

Biomass Quality Responses to Selection for Increased Biomass Yield in Perennial Energy Grasses - Michael D. Casler; DoKyoung Lee; Robert B. Mitchell; Kenneth J. Moore; Paul R. Adler; R. Mark Sulc; Keith D. Johnson; Robert L. Kallenbach; Arvid R. Boe; Russell D. Mathison; Kim A. Cassida; Doohong Min; et al. (BioEnergy Research, 2023)

Growth responses of mixotrophic giant clams on nearshore turbid coral reefs - Kimberley Mills; Eleanor H. John; Duncan D. Muir; Nadiezhda Santodomingo; Kenneth G. Johnson; Muhammad Ali Syed Hussein; Sindia Sosdian (Coral Reefs, 2023)
Increasing evidence suggests that nearshore turbid coral reefs may mitigate bleaching of reef building calcifiers and play a critical role in the future of marine biodiversity in coastal areas. However, biomineralization processes on turbid reefs are relatively understudied compared to clear water counterparts and most published work focuses on corals. Here, we investigate how the mixotrophic giant clam Tridacna squamosa , a bivalve with ecological, cultural and economic significance, grows across a mosaic of less turbid to turbid reefs in the Coral Triangle. We construct growth chronologies from live and dead collected shells by measuring daily growth increments with petrography and scanning electron microscopy (SEM) to gain insight into growth rate on daily, seasonal and annual scales. We find annual growth is not significantly different across a turbidity gradient when scaled to ontogeny, while seasonal growth highly varies. K d (490) (a measurement positively correlated with turbidity) and chlorophyll- a are likely important factors driving seasonal growth on a turbid reef near a river, compared to sea surface temperature (SST), cloud cover and rainfall on a less turbid reef. On a daily scale, we investigate increment microstructure and spectral characteristics of chronologies, finding a relationship between tidal range and daily increments. Overall, our results indicate that light-enhanced calcification is likely most important in the less turbid reef, compared to heterotrophic feeding in the turbid reef. The trophic plasticity of T. squamosa may allow for its sustained growth in marginal conditions, supporting evidence that these habitats serve as important conservation hotspots for diverse reef building taxa.

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Salt intake and gastric cancer: a pooled analysis within the Stomach cancer Pooling (StoP) Project - Samantha Morais; Adriana Costa; Gabriela Albuquerque; Natália Araújo; Claudio Pelucchi; Charles S. Rabkin; Linda M. Liao; Rashmi Sinha; Zuo-Feng Zhang; Jinfu Hu; Kenneth C. Johnson; Domenico Palli; et al. (Cancer Causes & Control, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

The Technological, Scientific, and Sociological Revolution of Global Subsurface Ocean Observing - Dean Roemmich; Lynne Talley; Nathalie Zilberman; Emily Osborne; Kenneth Johnson; Leticia Barbero; Henry Bittig; Nathan Briggs; Andrea Fassbender; Gregory Johnson; Brian King; Elaine McDonagh; et al. (Oceanography, 2021)

Delayed-Mode Quality Control of Oxygen, Nitrate, and pH Data on SOCCOM Biogeochemical Profiling Floats - Tanya L. Maurer; Joshua N. Plant; Kenneth S. Johnson (Frontiers in Marine Science, 2021)
The Southern Ocean Carbon and Climate Observations and Modeling (SOCCOM) project has deployed 194 profiling floats equipped with biogeochemical (BGC) sensors, making it one of the largest contributors to global BGC-Argo. Post-deployment quality control (QC) of float-based oxygen, nitrate, and pH data is a crucial step in the processing and dissemination of such data, as in situ chemical sensors remain in early stages of development. In situ calibration of chemical sensors on profiling floats using atmospheric reanalysis and empirical algorithms can bring accuracy to within 3 μmol O 2 kg –1 , 0.5 μmol NO 3 – kg –1 , and 0.007 pH units. Routine QC efforts utilizing these methods can be conducted manually through visual inspection of data to assess sensor drifts and offsets, but more automated processes are preferred to support the growing number of BGC floats and reduce subjectivity among delayed-mode operators. Here we present a methodology and accompanying software designed to easily visualize float data against select reference datasets and assess QC adjustments within a quantitative framework. The software is intended for global use and has been used successfully in the post-deployment calibration and QC of over 250 BGC floats, including all floats within the SOCCOM array. Results from validation of the proposed methodology are also presented which help to verify the quality of the data adjustments through time.

Nitrogen Demand Associated with Increased Biomass Yield of Switchgrass and Big Bluestem: Implications for Future Breeding Strategies - Michael D. Casler; DoKyoung Lee; Robert B. Mitchell; Paul R. Adler; R. Mark Sulc; Keith D. Johnson; Robert L. Kallenbach; Arvid R. Boe; Russell D. Mathison; Kim A. Cassida; Doohong Min; Kenneth J. Moore (BioEnergy Research, 2020)

Correction to: Status and trends of circumpolar peregrine falcon and gyrfalcon populations - Alastair Franke; Knud Falk; Kevin Hawkshaw; Skip Ambrose; David L. Anderson; Peter J. Bente; Travis Booms; Kurt K. Burnham; Suzanne Carrière; Johan Ekenstedt; Ivan Fufachev; Sergey Ganusevich; et al. (Ambio, 2020)

Status and trends of circumpolar peregrine falcon and gyrfalcon populations - Alastair Franke; Knud Falk; Kevin Hawkshaw; Skip Ambrose; David L. Anderson; Peter J. Bente; Travis Booms; Kurt K. Burnham; Johan Ekenstedt; Ivan Fufachev; Sergey Ganusevich; Kenneth Johansen; et al. (Ambio, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Resistance is futile: RNA-sequencing reveals differing responses to bat fungal pathogen in Nearctic Myotis lucifugus and Palearctic Myotis myotis - Thomas M. Lilley; Jenni M. Prokkola; Anna S. Blomberg; Steve Paterson; Joseph S. Johnson; Gregory G. Turner; Tomáš Bartonička; Erik Bachorec; DeeAnn M. Reeder; Kenneth A. Field (Oecologia, 2019)
Resistance and tolerance allow organisms to cope with potentially life-threatening pathogens. Recently introduced pathogens initially induce resistance responses, but natural selection favors the development of tolerance, allowing for a commensal relationship to evolve. Mycosis by Pseudogymnoascus destructans , causing white-nose syndrome (WNS) in Nearctic hibernating bats, has resulted in population declines since 2006. The pathogen, which spread from Europe, has infected species of Palearctic Myotis for a longer period. We compared ecologically relevant responses to the fungal infection in the susceptible Nearctic M. lucifugus and less susceptible Palearctic M. myotis , to uncover factors contributing to survival differences in the two species. Samples were collected from euthermic bats during arousal from hibernation, a naturally occurring phenomenon, during which transcriptional responses are activated. We compared the whole-transcriptome responses in wild bats infected with P. destructans hibernating in their natural habitat. Our results show dramatically different local transcriptional responses to the pathogen between uninfected and infected samples from the two species. Whereas we found 1526 significantly upregulated or downregulated transcripts in infected M. lucifugus , only one transcript was downregulated in M. myotis . The upregulated response pathways in M. lucifugus include immune cell activation and migration, and inflammatory pathways, indicative of an unsuccessful attempt to resist the infection. In contrast, M. myotis appears to tolerate P. destructans infection by not activating a transcriptional response. These host-microbe interactions determine pathology, contributing to WNS susceptibility, or commensalism, promoting tolerance to fungal colonization during hibernation that favors survival. Graphic abstract

Pattern and scale: evaluating generalities in crab distributions and marsh dynamics from small plots to a national scale - Kerstin Wasson; Kenneth Raposa; Monica Almeida; Kathryn Beheshti; Jeffrey A. Crooks; Anna Deck; Nikki Dix; Caitlin Garvey; Jason Goldstein; David Samuel Johnson; Scott Lerberg; Pamela Marcum; et al. (Ecology, 2019)
The generality of ecological patterns depends inextricably on the scale at which they are examined. We investigated patterns of crab distribution and the relationship between crabs and vegetation in salt marshes at multiple scales. By using consistent monitoring protocols across 15 U.S. National Estuarine Research Reserves, we were able to synthesize patterns from the scale of quadrats to the entire marsh landscape to regional and national scales. Some generalities emerged across marshes from our overall models, and these are useful for informing broad coastal management policy. We found that crab burrow distribution within a marsh could be predicted by marsh elevation, distance to creek and soil compressibility. While these physical factors also affected marsh vegetation cover, we did not find a strong or consistent overall effect of crabs at a broad scale in our multivariate model, though regressions conducted separately for each site revealed that crab burrows were negatively correlated with vegetation cover at 4 out of 15 sites. This contrasts with recent smaller‐scale studies and meta‐analyses synthesizing such studies that detected strong negative effects of crabs on marshes, likely because we sampled across the entire marsh landscape, while targeted studies are typically limited to low‐lying areas near creeks, where crab burrow densities are highest. Our results suggest that sea‐level rise generally poses a bigger threat to marshes than crabs, but there will likely be interactions between these physical and biological factors. Beyond these generalities across marshes, we detected some regional differences in crab community composition, richness, and abundance. However, we found striking differences among sites within regions, and within sites, in terms of crab abundance and relationships to marsh integrity. Although generalities are broadly useful, our findings indicate that local managers cannot rely on data from other nearby systems, but rather need local information for developing salt marsh management strategies.

A BGC-Argo Guide: Planning, Deployment, Data Handling and Usage - Henry C. Bittig; Tanya L. Maurer; Joshua N. Plant; Catherine Schmechtig; Annie P. S. Wong; Hervé Claustre; Thomas W. Trull; T. V. S. Udaya Bhaskar; Emmanuel Boss; Giorgio Dall’Olmo; Emanuele Organelli; Antoine Poteau; et al. (Frontiers in Marine Science, 2019)

On the Future of Argo: A Global, Full-Depth, Multi-Disciplinary Array - Dean Roemmich; Matthew H. Alford; Hervé Claustre; Kenneth Johnson; Brian King; James Moum; Peter Oke; W. Brechner Owens; Sylvie Pouliquen; Sarah Purkey; Megan Scanderbeg; Toshio Suga; et al. (Frontiers in Marine Science, 2019)

The association between coffee consumption and bladder cancer in the bladder cancer epidemiology and nutritional determinants (BLEND) international pooled study - Evan Yi-Wen Yu; Anke Wesselius; Frits van Osch; Mariana Carla Stern; Xuejuan Jiang; Eliane Kellen; Chih-Ming Lu; Hermann Pohlabeln; Gunnar Steineck; James Marshall; Mohamed Farouk Allam; Carlo La Vecchia; et al. (Cancer Causes & Control, 2019)

Riverscape genetic variation, migration patterns, and morphological variation of the threatened Round Rocksnail, Leptoxis ampla - Nathan V. Whelan; Matthew P. Galaska; Breanna N. Sipley; Jennifer M. Weber; Paul D. Johnson; Kenneth M. Halanych; Brian S. Helms (Molecular Ecology, 2019)
Within riverine systems, headwater populations are hypothesized to harbour higher amounts of genetic distinctiveness than populations in the main stem of a river and display increased genetic diversity in large, downstream habitats. However, these hypotheses were mostly developed with insects and fish, and they have not been tested on many invertebrate lineages. Pleuroceridae gastropods are of particular ecological importance to rivers of eastern North America, sometimes comprising over 90% of macroinvertebrate biomass. Yet, virtually nothing is known of pleurocerid landscape genetics, including whether genetic diversity follows predictions made by hypotheses developed on more mobile species. Moreover, the commonly repeated hypothesis that intraspecific morphological variation in gastropods results from ecophenotypic plasticity has not been well tested on pleurocerids. Using 2bRAD‐seq to discover single nucleotide polymorphisms, we show that the threatened, Cahaba River endemic pleurocerid, Leptoxis ampla, has limited gene flow among populations and that migration is downstream‐biased, conflicting with previous hypotheses. Both tributary and main stem populations harbour unique genomic profiles, and genetic diversity was highest in downstream populations. Furthermore, L. ampla shell morphology was more correlated with genetic differences among individuals and populations than habitat characteristics. We anticipate similar genetic and demographic patterns to be seen in other pleurocerids, and hypotheses about gene flow and population demographics that were based on more mobile taxa often, but not always, apply to freshwater gastropods. From a conservation standpoint, genetic structure of L. ampla populations suggests distinctive genetic diversity is lost with localized extirpation, a phenomenon common across the range of Pleuroceridae.

Genetic variation in thyroid folliculogenesis influences susceptibility to hypothyroidism-induced hearing impairment - Amanda H. Mortensen; Qing Fang; Michelle T. Fleming; Thomas J. Jones; Alexandre Z. Daly; Kenneth R. Johnson; Sally A. Camper (Mammalian Genome, 2019)

The Influence of Human Demography on Land Cover Change in the Great Lakes States, USA - Mark J. Ducey; Kenneth M. Johnson; Ethan P. Belair; Barbara D. Cook (Environmental Management, 2018)

Effect of torpor on host transcriptomic responses to a fungal pathogen in hibernating bats - Kenneth A. Field; Brent J. Sewall; Jenni M. Prokkola; Gregory G. Turner; Marianne F. Gagnon; Thomas M. Lilley; J. Paul White; Joseph S. Johnson; Christopher L. Hauer; DeeAnn M. Reeder (Molecular Ecology, 2018)
Hibernation, the use of prolonged torpor to depress metabolism, is employed by mammals to conserve resources during extended periods of extreme temperatures and/or resource limitation. Mammalian hibernators arouse to euthermy periodically during torpor for reasons that are not well understood, and these arousals may facilitate immune processes. To determine whether arousals enable host responses to pathogens, we used dual RNA ‐Seq and a paired sampling approach to examine gene expression in a hibernating bat, the little brown myotis ( Myotis lucifugus ). During torpor, transcript levels differed in only a few genes between uninfected wing tissue and adjacent tissue infected with Pseudogymnoascus destructans , the fungal pathogen that causes white‐nose syndrome. Within 70–80 min after emergence from torpor, large changes in gene expression were observed due to local infection, particularly in genes involved in pro‐inflammatory host responses to fungal pathogens, but also in many genes involved in immune responses and metabolism. These results support the hypothesis that torpor is a period of relative immune dormancy and arousals allow for local immune responses in infected tissues during hibernation. Host–pathogen interactions were also found to regulate gene expression in the pathogen differently depending on the torpor state of the host. Hibernating species must balance the benefits of energy and water conservation achieved during torpor with the costs of decreased immune competence. Interbout arousals allow hibernators to optimize these, and other, trade‐offs during prolonged hibernation by enabling host responses to pathogens within brief, periodic episodes of euthermy.

Tropicalization of the Northern Gulf of Mexico: Impacts of Salt Marsh Transition to Black Mangrove Dominance on Faunal Communities - Whitney A. Scheffel; Kenneth L. Heck; Matthew W. Johnson (Estuaries and Coasts, 2018)

Vertically challenged: How disease suppresses Daphnia vertical migration behavior - Pieter T. J. Johnson; Daniel E. Stanton; Kenneth J. Forshay; Dana M. Calhoun (Limnology and Oceanography, 2018)
Parasitic infections are increasingly recognized as influential forces in the migratory behaviors of hosts ranging from butterflies to whales. In aquatic zooplankton, diel vertical migrations (DVMs) are among the most recurrent behaviors with implications for predator‐prey interactions, nutrient cycling, and energy flow, yet how parasitism affects such migrations remains an open question. Here, we tested the effects of sporangia cluster disease (SCD) on DVM of the large‐bodied Daphnia pulicaria , which is often considered a key component of lake food webs. By collecting depth‐specific zooplankton samples across diel cycles, between years, and among lakes, we show that infection is associated with strong inhibition of host DVM; while all Daphnia tended to occur deeper during the day, uninfected Daphnia and especially gravid individuals migrated to shallower waters at night. In contrast, infected hosts—which could comprise 40% of the population—were more likely to remain deep regardless of time of day. Among infected hosts, the intensity of SCD (sporangia count per host) predicted the degree of DVM inhibition. These observations—coupled with lab‐based assays showing that infected hosts exhibited fewer swimming movements and persisted at lower depths than uninfected conspecifics—suggest that parasite‐induced inhibition of DVM is a “sickness behavior” resulting from increasing morbidity and energy depletion as the infection intensifies toward host death. Considering the importance of large‐bodied Daphnia as regulators of water clarity and prey for fishes, parasite‐induced alterations of host migratory behavior have broad potential to affect the redistribution of energy and nutrients within lake ecosystems.

Oxygen Optode Sensors: Principle, Characterization, Calibration, and Application in the Ocean - Henry C. Bittig; Arne Körtzinger; Craig Neill; Eikbert van Ooijen; Joshua N. Plant; Johannes Hahn; Kenneth S. Johnson; Bo Yang; Steven R. Emerson (Frontiers in Marine Science, 2018)

Energy conserving thermoregulatory patterns and lower disease severity in a bat resistant to the impacts of white-nose syndrome - Marianne S. Moore; Kenneth A. Field; Melissa J. Behr; Gregory G. Turner; Morgan E. Furze; Daniel W. F. Stern; Paul R. Allegra; Sarah A. Bouboulis; Chelsey D. Musante; Megan E. Vodzak; Matthew E. Biron; Melissa B. Meierhofer; et al. (Journal of Comparative Physiology B, 2018)

Facilitators of Survivorship Care Among Underserved Breast Cancer Survivors: a Qualitative Study - Amy E. Ustjanauskas; Gwendolyn P. Quinn; Tonya M. Pan; Maria Rivera; Coralia Vázquez-Otero; Danielle Ung; Richard G. Roetzheim; Christine Laronga; Kenneth Johnson; Marilyn Norton; Claudia Carrizosa; Dariana Muñoz; et al. (Journal of Cancer Education, 2017)

Hourly In Situ Nitrate on a Coastal Mooring: A 15-Year Record and Insights into New Production - Carole Sakamoto; Kenneth Johnson; Luke Coletti; Tanya Maurer; Gene Massion; J. Timothy Pennington; Joshua Plant; Hans Jannasch; Francisco Chavez (Oceanography, 2017)

Assessment of sweet cherry (Prunus avium L.) genotypes for response to bacterial canker disease - Josephine Mgbechi-Ezeri; Lyndon Porter; Kenneth B. Johnson; Nnadozie Oraguzie (Euphytica, 2017)

The Argo Program: Present and Future - Steven Jayne; Dean Roemmich; Nathalie Zilberman; Stephen Riser; Kenneth Johnson; Gregory Johnson; Stephen Piotrowicz (Oceanography, 2017)

Estimates of Water-Column Nutrient Concentrations and Carbonate System Parameters in the Global Ocean: A Novel Approach Based on Neural Networks - Raphaëlle Sauzède; Henry C. Bittig; Hervé Claustre; Orens Pasqueron de Fommervault; Jean-Pierre Gattuso; Louis Legendre; Kenneth S. Johnson (Frontiers in Marine Science, 2017)

Aerosols in the Pre-industrial Atmosphere - Kenneth S. Carslaw; Hamish Gordon; Douglas S. Hamilton; Jill S. Johnson; Leighton A. Regayre; M. Yoshioka; Kirsty J. Pringle (Current Climate Change Reports, 2017)

Paleoenvironmental conditions of Early Miocene corals, western Makran, Iran - Mehdi Ghaedi; Kenneth Johnson; Mehdi Yazdi (Arabian Journal of Geosciences, 2016)

Understanding the murky history of the Coral Triangle: Miocene corals and reef habitats in East Kalimantan (Indonesia) - Nadiezhda Santodomingo; Willem Renema; Kenneth G. Johnson (Coral Reefs, 2016)

A hypomorphic mutation of the gamma-1 adaptin gene (Ap1g1) causes inner ear, retina, thyroid, and testes abnormalities in mice - Kenneth R. Johnson; Leona H. Gagnon; Bo Chang (Mammalian Genome, 2016)

Neuropsychological, Neurovirological and Neuroimmune Aspects of Abnormal GABAergic Transmission in HIV Infection - Tetyana Buzhdygan; Joshua Lisinicchia; Vipulkumar Patel; Kenneth Johnson; Volker Neugebauer; Slobodan Paessler; Kristofer Jennings; Benjamin Gelman (Journal of Neuroimmune Pharmacology, 2016)

A sustainable museum collection of historical imagery for coral reef baselines - Robert Yarlett; Francoise Cavada; Judith Lang; Kenneth G. Johnson (Coral Reefs, 2016)

Association of genetic susceptibility variants for type 2 diabetes with breast cancer risk in women of European ancestry - Zhiguo Zhao; Wanqing Wen; Kyriaki Michailidou; Manjeet K. Bolla; Qin Wang; Ben Zhang; Jirong Long; Xiao-Ou Shu; Marjanka K. Schmidt; Roger L. Milne; Montserrat García-Closas; Jenny Chang-Claude; et al. (Cancer Causes & Control, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Bias and Efficiency Tradeoffs in the Selection of Storm Suites Used to Estimate Flood Risk - Jordan Fischbach; David Johnson; Kenneth Kuhn (Journal of Marine Science and Engineering, 2016)
Modern joint probability methods for estimating storm surge or flood statistics are based on statistical aggregation of many hydrodynamic simulations that can be computationally expensive. Flood risk assessments that consider changing future conditions due to sea level rise or other drivers often require each storm to be run under a range of uncertain scenarios. Evaluating different flood risk mitigation measures, such as levees and floodwalls, in these future scenarios can further increase the computational cost. This study uses the Coastal Louisiana Risk Assessment model (CLARA) to examine tradeoffs between the accuracy of estimated flood depth exceedances and the number and type of storms used to produce the estimates. Inclusion of lower-intensity, higher-frequency storms significantly reduces bias relative to storm suites with a similar number of storms but only containing high-intensity, lower-frequency storms, even when estimating exceedances at very low-frequency return periods.

Nitrogen Retention in Salt Marsh Systems Across Nutrient-Enrichment, Elevation, and Precipitation Regimes: a Multiple-Stressor Experiment - Autumn Oczkowski; Cathleen Wigand; Alana Hanson; Erin Markham; Kenneth M. Miller; Roxanne Johnson (Estuaries and Coasts, 2016)

Erratum to: Influence of Location, Year, Potato Rotation, and Chemical Seed Treatment on Incidence and Severity of Silver Scurf on Progeny Tubers - Jeffrey S. Miller; Philip B. Hamm; Jeremiah K. S. Dung; Brad D. Geary; Steven R. James; Dennis A. Johnson; Kenneth Rykbost (American Journal of Potato Research, 2015)

A QTL on Chr 5 modifies hearing loss associated with the fascin-2 variant of DBA/2J mice - Kenneth R. Johnson; Chantal M. Longo-Guess; Leona H. Gagnon (Mammalian Genome, 2015)

Influence of Location, Year, Potato Rotation, and Chemical Seed Treatment on Incidence and Severity of Silver Scurf on Progeny Tubers - Jeffrey S. Miller; Philip B. Hamm; Jeremiah K. S. Dung; Brad D. Geary; Steven R. James; Dennis A. Johnson; Kenneth Rykbost (American Journal of Potato Research, 2015)

Development of polymorphic microsatellite markers for the orange-breasted falcon (Falco deiroleucus) - Rochelle R. Beasley; Stacey L. Lance; Kenneth L. Jones; Robert B. Berry; Jeff A. Johnson (Conservation Genetics Resources, 2014)

Grassland fires may favor native over introduced plants by reducing pathogen loads - Bitty A. Roy; Kenneth Hudson; Matt Visser; Bart R. Johnson (Ecology, 2014)
Grasslands have been lost and degraded in the United States since Euro‐American settlement due to agriculture, development, introduced invasive species, and changes in fire regimes. Fire is frequently used in prairie restoration to control invasion by trees and shrubs, but may have additional consequences. For example, fire might reduce damage by herbivore and pathogen enemies by eliminating litter, which harbors eggs and spores. Less obviously, fire might influence enemy loads differently for native and introduced plant hosts. We used a controlled burn in a Willamette Valley (Oregon) prairie to examine these questions. We expected that, without fire, introduced host plants should have less damage than native host plants because the introduced species are likely to have left many of their enemies behind when they were transported to their new range (the enemy release hypothesis, or ERH). If the ERH holds, then fire, which should temporarily reduce enemies on all species, should give an advantage to the natives because they should see greater total reduction in damage by enemies. Prior to the burn, we censused herbivore and pathogen attack on eight plant species (five of nonnative origin: Bromus hordaceous , Cynosuros echinatus , Galium divaricatum , Schedonorus arundinaceus (= Festuca arundinacea ), and Sherardia arvensis ; and three natives: Danthonia californica , Epilobium minutum , and Lomatium nudicale ). The same plots were monitored for two years post‐fire. Prior to the burn, native plants had more kinds of damage and more pathogen damage than introduced plants, consistent with the ERH. Fire reduced pathogen damage relative to the controls more for the native than the introduced species, but the effects on herbivory were negligible. Pathogen attack was correlated with plant reproductive fitness, whereas herbivory was not. These results suggest that fire may be useful for promoting some native plants in prairies due to its negative effects on their pathogens.

Fortnightly Tidal Modulations Affect Net Community Production in a Mesotidal Estuary - Nicholas J. Nidzieko; Joseph A. Needoba; Stephen G. Monismith; Kenneth S. Johnson (Estuaries and Coasts, 2014)

A comparison of Mediterranean Gecko (Hemidactylus turcicus) populations in two temperate zone urban habitats - L. Brooke Stabler; Whittney L. Johnson; Kenneth J. Locey; Paul A. Stone (Urban Ecosystems, 2012)

Prefrontal Dopaminergic and Enkephalinergic Synaptic Accommodation in HIV-associated Neurocognitive Disorders and Encephalitis - Benjamin B. Gelman; Joshua G. Lisinicchia; Tianshen Chen; Kenneth M. Johnson; Kristofer Jennings; Daniel H. Freeman; Vicki M. Soukup (Journal of Neuroimmune Pharmacology, 2012)

Assessing the effects of chronic sazetidine-A delivery on nicotine self-administration in both male and female rats - Joshua E. Johnson; Susan Slade; Corinne Wells; Ann Petro; Hannah Sexton; Amir H. Rezvani; Milton L. Brown; Mikell A. Paige; Brian E. McDowell; Yingxian Xiao; Kenneth J. Kellar; Edward D. Levin (Psychopharmacology, 2012)

Pacific Rim Forestry / Silviculture and Forest Ecology - Vishal Singh Negi; Archana Pal; Ratnesh Singh; Dulal Borthakur; Archana Pala; Vishal Singh Negi; Dulal Borthakur; Isabel Rushanaedy; Tyler Jones; Nicklos Dudley; Dulal Borthakur; Jannai Yafuso; et al. (Journal of Forestry, 2011)
Leucaena leucocephala (leucaena) is an important agroforestry tree of tropics and subtropics due to its protein rich foliages, ability to grow on poor soils, and high level of tolerance to various stresses including drought and diseases. We hypothesized that leucaena have a unique set of genes which confer tolerance to various abiotic and biotic stresses and these genes are either absent or not expressed in other legumes that are susceptible to these stress conditions. Interspecies suppression subtractive hybridization (iSSH) was performed to identify some unique genes from leucaena using cDNAs from leucaena and Acacia confusa (acacia) as the tester and driver, respectively. We identified 100 leucaena genes showing homology to various plant genes with known functions, of which 23 genes had homology to various stress-related proteins including chitinase, PR-10 protein, wound-stress protein, type-2 metallothionein, thaumatin-like protein, disease resistance response protein, cysteine proteinase, and kunitz trypsin inhibitor. We also identified 50 leucaena genes which either had homology to hypothetical proteins (HyPs) or had no homology at all. Putative functions of 15 HyPs were predicted using conserved domain and PSI-BLAST analyses. Linear motif analyses identified 17 HyPs with MAPK recognition motif, which is involved in signaling pathways, including stress responses. This study identified 23 known and some putative unique stress-related genes from leucaena which may serve as a useful source of stress-tolerance genes for tree and crop improvement in the future.

Chytrid infection reduces thoracic beat and heart rate of Daphnia pulicaria - D. C. Peñalva-Arana; Kenneth Forshay; Pieter T. J. Johnson; J. R. Strickler; Stanley I. Dodson (Hydrobiologia, 2011)

Simultaneous measurements of nitrate, oxygen, and carbon dioxide on oceanographic moorings: Observing the Redfield Ratio in real time - Kenneth S. Johnson (Limnology and Oceanography, 2010)
Autonomous observations of dissolved nitrate, oxygen, and total inorganic carbon (TCO 2 , which is derived from pCO 2 and estimates of alkalinity) from sensors on the M1 and M2 moorings, off Monterey Bay, California, are examined. These observations are used to assess the linkages between nitrogen, oxygen, and carbon cycling with the Redfield ratio as a framework for the analysis. Concentrations of TCO 2 , oxygen, and nitrate were highpass filtered to remove low‐frequency signals driven by water mass changes. Daily cycles in each property are apparent with maxima or minima at the end of daylight. These daily cycles are consistent with biological production of oxygen or uptake of TCO 2 and nitrate. Ratios of the changes in these diel cycles approach values expected from the Redfield ratio early in upwelling cycles. However, periods are frequently seen where the utilization of nitrate N is substantially lower than expected when compared to observed changes in TCO 2 or oxygen. During these periods, fixed nitrogen must be supplied from other sources, such as ammonium or urea, or it is obtained from deeper waters by vertically migrating phytoplankton. These migrating phytoplankton must then return to the surface where inorganic carbon is consumed and oxygen is produced.

No Differences in Soil Carbon Stocks Across the Tree Line in the Peruvian Andes - Michael Zimmermann; Patrick Meir; Miles R. Silman; Anna Fedders; Adam Gibbon; Yadvinder Malhi; Dunia H. Urrego; Mark B. Bush; Kenneth J. Feeley; Karina C. Garcia; Greta C. Dargie; Wiliam R. Farfan; et al. (Ecosystems, 2010)

Recreational physical activity and the risk of adult leukemia in Canada - Khaled Kasim; Kenneth C. Johnson; Patrick Levallois; Belkacem Abdous; Pierre Auger (Cancer Causes & Control, 2009)

Observing Biogeochemical Cycles at Global Scales with Profiling Floats and Gliders: Prospects for a Global Array - Kenneth Johnson; William Berelson; Emmanuel Boss; Zanna Chase; Hervé Claustre; Steven Emerson; Nicolas Gruber; Arne Körtzinger; Mary Jane Perry; Stephen Riser (Oceanography, 2009)

The podosomal-adaptor protein SH3PXD2B is essential for normal postnatal development - Mao Mao; Daniel R. Thedens; Bo Chang; Belinda S. Harris; Qing Yin Zheng; Kenneth R. Johnson; Leah Rae Donahue; Michael G. Anderson (Mammalian Genome, 2009)

Lung-to-lung circulation times during exercise in heart failure - Norman R. Morris; Eric M. Snyder; Kenneth C. Beck; Bruce D. Johnson (European Journal of Applied Physiology, 2009)

Spatiotemporal patterns of wetland occurrence in the Prairie Pothole Region of eastern South Dakota - Sharon N. Kahara; Rachel M. Mockler; Kenneth F. Higgins; Steven R. Chipps; Rex R. Johnson (Wetlands, 2009)

Ocean metabolism observed with oxygen sensors on profiling floats in the South Pacific - Todd R. Martz; Kenneth S. Johnson; Stephen C. Riser (Limnology and Oceanography, 2008)
We estimated rates of production and export in the South Pacific (80°W to 180°W in a zonal band between 35°S and 50°S) using 1.5 yr of oxygen measurements from profiling floats. Export production, calculated from oxygen utilization rates below the compensation depth from December to April, was 10.7 ± 2 mmol C m −2 d −1 ( n = 36, 95% CI). The corresponding satellite net primary production was 46 ± 4 mmol C m −2 d −1 , yielding a regional e‐ratio of 0.23 ± 0.05. Averaging oxygen utilization rates resulted in a net cancellation of most water mass changes related to advection and float migration. The composite vertical profile of remineralization rates, obtained by binning 36 rate profiles, agreed with published measurements based on oxygen utilization rates in hydrographic surveys and fits the classic form of a particulate organic carbon (POC) attenuation function. However, the disagreement between oxygen‐based remineralization rates and those obtained by sediment traps suggests fundamental differences between these two methods. Using float data to constrain a one‐dimensional mixed‐layer model, the annual net community production at 45°S, 144°W was ~2.5 mol C m −2 d −1 . Spatial trends in export production coinciding with the New Zealand shelf and Subtropical Front are identified.

Mapping the spatial variability of plankton metabolism using nitrate and oxygen sensors on an autonomous underwater vehicle - Kenneth S. Johnson; Joseph A. Needoba (Limnology and Oceanography, 2008)
It is now possible to make highly resolved vertical ( K Z × δ 2 NO 3 − /δZ 2 ( K Z = vertical eddy diffusion coefficient). Water column regions exhibiting elevated nitrate uptake rates are identified from anomalies in the second derivatives of the vertical concentration profiles relative to the second derivative of conservative properties. The relationship between chlorophyll a fluorescence and the inferred productivity rates exhibits coherent spatial variability across the bay.

Two new species of the side necked turtle genus,Bairdemys (Pleurodira, Podocnemididae), from the Miocene of Venezuela - Eugene S. Gaffney; Torsten M. Scheyer; Kenneth G. Johnson; Jean Bocquentin; Orangel A. Aguilera (PalZ, 2008)

The Collaborative Cross at Oak Ridge National Laboratory: developing a powerful resource for systems genetics - Elissa J. Chesler; Darla R. Miller; Lisa R. Branstetter; Leslie D. Galloway; Barbara L. Jackson; Vivek M. Philip; Brynn H. Voy; Cymbeline T. Culiat; David W. Threadgill; Robert W. Williams; Gary A. Churchill; Dabney K. Johnson; et al. (Mammalian Genome, 2008)

Targeted knockout and lacZ reporter expression of the mouse Tmhs deafness gene and characterization of the hscy-2J mutation - Chantal M. Longo-Guess; Leona H. Gagnon; Bernd Fritzsch; Kenneth R. Johnson (Mammalian Genome, 2007)

Dietary thyroid hormone replacement ameliorates hearing deficits in hypothyroid mice - I. Jill Karolyi; Gary A. Dootz; Karin Halsey; Lisa Beyer; Frank J. Probst; Kenneth R. Johnson; Albert F. Parlow; Yehoash Raphael; David F. Dolan; Sally A. Camper (Mammalian Genome, 2007)

In vivo pharmacological characterization of the structurally novel, potent, selective mGlu2/3 receptor agonist LY404039 in animal models of psychiatric disorders - Linda M. Rorick-Kehn; Bryan G. Johnson; Karen M. Knitowski; Craig R. Salhoff; Jeffrey M. Witkin; Kenneth W. Perry; Kelly I. Griffey; Joseph P. Tizzano; James A. Monn; David L. McKinzie; Darryle D. Schoepp (Psychopharmacology, 2007)

Nitrogen fixation by unicellular diazotrophic cyanobacteria in the temperate oligotrophic North Pacific Ocean - Joseph A. Needoba; Rachel A. Foster; Carole Sakamoto; Jonathan P. Zehr; Kenneth S. Johnson (Limnology and Oceanography, 2007)
N 2 fixation has been understudied in marine environments outside of the subtropical and tropical oceans and where water temperatures are typically below 20‐25°C. We identified nifH phylotypes and measured N 2 fixation rates under ambient conditions (maximum of 19°C) in water collected 750 km off the coast of California in oligotrophic waters of the North Pacific Ocean (34°N, 129°W). Near‐surface N 2 fixation rates averaged 0.25 ± 0.05 nmol N L −1 d −1 for 24 incubation bottles. Despite low ambient concentrations of iron ( −1 ) and phosphorus ( −1 ), N 2 fixation rates were unaffected by iron and phosphorus amendments. Using reverse transcription‐quantitative polymerase chain reaction (RT‐QPCR) methodology, we estimated transcript abundance and patterns of expression for several unicellular diazotrophs, including the group A phylotype, which showed the highest daily mRNA abundances. The N 2 ‐fixing assemblage extended to 60‐80 m depth, well below the seasonal thermocline (40 m). The calculated areal N 2 fixation rate (15 µmol N m −2 d −1 ) was small compared with estimates from other regions of the Pacific; however, the estimated fixation rate was similar to other published results, suggesting that processes other than cellular growth rate may determine the abundance of unicellular diazotrophs. Despite the low N 2 fixation rates, the new nitrogen added to the euphotic zone by N 2 fixation could account for at least 10% of new production during the study period.

Seagrass patch characteristics alter direct and indirect interactions in a tritrophic estuarine food web - Matthew W. Johnson; Kenneth L. Heck (Estuaries and Coasts, 2006)

Evaluation of cardiac output from a tidally ventilated homogeneous lung model - Habib Benallal; Kenneth C. Beck; Bruce D. Johnson; Thierry Busso (European Journal of Applied Physiology, 2005)

Lifestyle factors and the risk of adult leukemia in Canada - Khaled Kasim; Patrick Levallois; Belkacem Abdous; Pierre Auger; Kenneth C. Johnson (Cancer Causes & Control, 2005)

Coastal Ocean Physics and Red Tides: An Example from Monterey Bay, California - John Ryan; Heidi Dierssen; Raphael Kudela; Christopher Scholin; Kenneth Johnson; James Sullivan; Andrew Fischer; Erich Rienecker; Patrick McEnaney; Francisco Chavez (Oceanography, 2005)

A case?control study of occupational risk factors for bladder cancer in Canada - Reimar R. W. Gaertner; Ljiljana Trpeski; Kenneth C. Johnson (Cancer Causes & Control, 2004)

Amphibians and Fire in Longleaf Pine Ecosystems: Response to Schurbon and Fauth - D. BRUCE MEANS; C. KENNETH DODD; STEVE A. JOHNSON; JOHN G. PALIS (Conservation Biology, 2004)

New intragenic deletions in the Phex gene clarify X-linked hypophosphatemia-related abnormalities in mice - Leona H. Gagnon; Joiel D. Bauschatz; Muriel T. Davisson; Linda L. Washburn; Leah Rae Donahue; Tim M. Strom; Eva M. Eicher; Kenneth R. Johnson; Victoria E. Guido; Bettina Lorenz-Depiereux; Qing Yin Zheng (Mammalian Genome, 2004)

Oxidative strand scission of nucleic acids by a multinuclear copper(II) complex - Kristi J. Humphreys; Anne E. Johnson; Kenneth D. Karlin; Steven E. Rokita (JBIC Journal of Biological Inorganic Chemistry, 2002)

McCauley Sinks: A compound breccia pipe in evaporite karst, Holbrook basin, Arizona, U.S.A. - James T. Neal; Kenneth S. Johnson (Carbonates and Evaporites, 2002)

Karst in evaporite rocks of the United States - Kenneth S. Johnson (Carbonates and Evaporites, 2002)

Preface to a Symposium on Evaporite Karst - Kenneth S. Johnson; Gültekin Günay (Carbonates and Evaporites, 2002)

Animal-related occupations and the risk of leukemia, myeloma, and non-Hodgkin's lymphoma in Canada - Lin Fritschi; Kenneth C. Johnson; Erich V. Kliewer; Rick Fry (Cancer Causes & Control, 2002)

A landscape approach to conserving wetland bird habitat in the prairie pothole region of eastern South Dakota - David E. Naugle; Rex R. Johnson; Michael E. Estey; Kenneth F. Higgins (Wetlands, 2001)

A landscape approach to conserving wetland bird habitat in the Prairie Pothole Region of eastern South Dakota - David E. Naugle; Rex R. Johnson; Michael E. Estey; Kenneth F. Higgins (Wetlands, 2000)

Grey intense: a new mouse mutation affecting pigmentation - Muriel T. Davisson; Kenneth R. Johnson; Roderick T. Bronson; Patricia F. Ward-Bailey; Susan A. Cook; Belinda S. Harris; Leah Rae Donahue (Mammalian Genome, 2000)

Neuromuscular ataxia: a new spontaneous mutation in the mouse - Patricia F. Ward-Bailey; Bonnie Wood; Kenneth R. Johnson; Rod T. Bronson; Leah Rae Donahue; Muriel T. Davisson (Mammalian Genome, 2000)

Temporal distribution of waterfowl in eastern South Dakota: Implications for aerial surveys - David E. Naugle; Rex R. Johnson; Thomas R. Cooper; Matthew M. Holland; Kenneth F. Higgins (Wetlands, 2000)

Passive and active smoking and breast cancer risk in Canada, 1994–97 - Kenneth C. Johnson; Jinfu Hu; Yang Mao (Cancer Causes & Control, 2000)

Risk factors for prostate cancer: results from the Canadian National Enhanced Cancer Surveillance System - Paul J. Villeneuve; Kenneth C. Johnson; Nancy Kreiger; Yang Mao (Cancer Causes & Control, 1999)

Lens epithelial proliferation cataract in segmental trisomy involving mouse Chromosomes 4 and 17 - Richard S. Smith; Kenneth R. Johnson; Norman L. Hawes; Belinda S. Harris; John P. Sundberg; Muriel T. Davisson (Mammalian Genome, 1999)

Mouse chromosome 18 - Kenneth R. Johnson; Muriel T. Davisson (Mammalian Genome, 1998)

The original shaker-with-syndactylism mutation ( sy ) is a contiguous gene deletion syndrome - Kenneth R. Johnson; Susan A. Cook; Qing Yin Zheng (Mammalian Genome, 1998)

Bias in quadrat-derived estimates of number of prairie wetlands - Rex R. Johnson; Kenneth F. Higgins (Wetlands, 1998)

Chromosomal locations of the mouse fatty acid oxidation genes Cpt1a, Cpt1b, Cpt2, Acadvl, and metabolically related Crat gene - Keith B. Cox; Kenneth R. Johnson; Philip A. Wood (Mammalian Genome, 1998)

Accurate headspace analysis of ƒCO 2 in discrete water samples using batch equilibration - Craig Neill; Kenneth M. Johnson; Ernie Lewis; Douglas W. R. Wallace (Limnology and Oceanography, 1997)
A high‐accuracy, batch‐equilibration, static‐headspace technique for the determination of the fugacity of CO 2 ( f CO 2 ) in discrete water samples is described. The technique was designed for monitoring small changes of CO 2 in the ocean and has accuracy and precision ( 2 and C T , is comparable to or better than is generally attained using potentiometric titration. Compared with C T and total alkalinity measurements, the small sample volume and rapid analysis time makes it practical to perform analysis of multiple replicates in order to improve confidence in the result. The method is readily applicable to experimental studies such as incubations as well as to time‐series measurements of in situ biological metabolism. Because the analysis employsgas chromatography, the technique can be acapted to measure simultaneously a suite of gases dissolved in seawater.

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)

Evaporite karst in the United States - Kenneth S. Johnson (Carbonates and Evaporites, 1997)

Preface to a Symposium on Evaporite Karst: Origins, Processes, Landforms, Examples, and Impacts - Kenneth S. Johnson; James T. Neal (Carbonates and Evaporites, 1997)

The historical development of interferons as multiple sclerosis therapies - Kenneth P. Johnson (Journal of Molecular Medicine, 1997)

Mouse chromosome 18 - Kenneth R. Johnson; Muriel T. Davisson (Mammalian Genome, 1997)

Sex linkage in salmonids: Evidence from a hybridized genome of brook trout and arctic charr - Bernie May; Kenneth R. Johnson; James E. Wright (Biochemical Genetics, 1989)

Electrophoretic analysis of genetic linkage in Scots pine (Pinus sylvestris L.) - Charles R. Niebling; Kenneth Johnson; Henry D. Gerhold (Biochemical Genetics, 1987)

Joint segregation of biochemical loci in Salmonidae. III. Linkage associations in Salmonidae including data from rainbow trout (Salmo gairdneri) - Bernie May; James E. Wright; Kenneth R. Johnson (Biochemical Genetics, 1982)